Aktivitas Antibakteri Ekstrak Etanol Daun Pazote (Chenopodium ambrosioides L) Terhadap Escherichia coli - Djois Sugiaty Rintjap; Roske Irma Korobu; Lidya E S Rumajar (Jurnal Farmasi dan Ilmu Pengobatan, 2018)
Infectious diseases still remain a major problem in tropical countries like Indonesia. Uncontrolled of antimicrobials consumption leads to the emergence of resistance. So new antimicrobial searches need to be carried out. One of the plants suspected of having antimicrobial activity was Pazote (Chenopodium ambrosioides L.). Extraction of C. ambrosioides leaves was carried out by maceration with 70% ethanol. Antimicrobial activity was carried out by Kirby-Bauer (modified) at concentrations of 5, 10, and 15% while the inhibitory zone was observed daily for 3 days. The results showed that the duration of contact did not affect to the diameter of the inhibitory zone. The largest inhibitory diameter is indicated by 15% was 12.33 mm. In addition, the ethanol extract of C. ambrosioides leaves has the potential as an antimicrobial against Escherichia coli.